ANALISIS GAYA BAHASA PADA LIRIK LAGU DALAM ALBUM DALAM DINAMIKA KARYA PERUNGGU - Fajrianto Setyo Nugroho; Kodrat Eko Putro Setiawan (Universitas Hamzanwadi, 2026)
The purpose of this study is to identify the various types of figurative language used in the song lyrics of the album Dalam Dinamika by Perunggu. The scope of this research focuses specifically on the stylistic devices embedded within the lyrics of the Dalam Dinamika album. This study employs a qualitative approach with a descriptive design. The data source of this research is the Dalam Dinamika album by Perunggu, which consists of nine songs: (1) Tapi, (2) Amalan Baik, (3) Gemilang, (4) Pikiran Yang Matang, (5) Biarkan Ia Tumbuh, (6) Berita Buruk, (7) Aku Ada Untukmu, (8) Berhasil, and (9) Abu. The data collection techniques include reading and note-taking. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results of this study revealed a total of 83 instances of figurative language, comprising 61 instances of comparative language, 16 instances of repetitive language, 4 instances of contrastive language, and 2 instances of emphatic language. Additionally, the findings highlight an intriguing insight: musicians share a strong resemblance to literary writers. Much like writers, musicians carefully consider rhetorical devices, employing various forms of figurative language to craft their work.